The First Hormone: Adrenaline. (June 2019) - Rao, Yi
Abstract : It is not often that three misconceptions are associated with one molecule for more than a century. This is the case with adrenaline. The aim here is to clarify that adrenaline was the first hormone, with the discovery of its activity and chemical purification being prior to secretin. Adrenaline is the correct name given by Jōkichi Takamine, epinephrine being its inactive benzoyl derivative.